The nature of entrepreneurial orientation strength: the impact of shared values on firm performance - Weinzimmer, Laurence G.; Michel, Eric J.; Robin, Jennifer (Journal of Management & Organization, 2021)
Drawing on Wales, Monsen, and McKelvie's (2011, Entrepreneurship Theory and Practice, 35(5), 895–923) model of entrepreneurial orientation pervasiveness and the strong culture hypothesis (Denison, 1984, Organization Dynamics, 13, 4–22), this study investigates how entrepreneurial orientation (EO) strength, defined as the level of agreement in the shared perceptions of EO, serves as a boundary condition of the EO–firm performance relationship. Four field studies provide evidence for a valid and reliable 10-item multidimensional measure of entrepreneurial orientation, the EO-10, which in turn, may be used to assess EO strength. We establish content and construct validity of the EO-10 (study 1; n = 447 employees), criterion-related validity with revenue growth and sales growth (study 2; n = 412 employees in 43 profit centers), and convergent validity with Covin and Slevin's (1989, Strategic Management Journal, 10, 75–87) 9-item measure (study 3; n = 291 employees). Finally, in study 4 (n = 853 employees nested in 22 organizations), we demonstrate the interactive effects of EO and EO strength on profit growth and revenue growth. In sum, this study provides conceptual and empirical evidence for the importance of EO strength as a moderator of the EO–firm performance relationship.
0 citations (Crossref) [2023-10-31]
Keywords: Culture; dept.bus; entrepreneurial orientation strength; firm performance; peer-reviewed; scale development